PENERAPAN MEDIA KUIS INTERAKTIF KAHOOT UNTUK MENINGKATKAN SPEAKING SKILL DI DESA SUBANG - Anita Anggraeni; Cynantia Rachmijati; Dewi Listia Apriliyanti (IKIP SILIWANGI, 2020)
Characteristics compared to those who are more mature. They generally have a high curiosity but low attention span therefore different learning methods and techniques are needed. With the development of technology, more technology-based learning techniques are being implemented. The level of education in Desa Jalancagak Subang, which is still uneven, requires refreshing learning methods, especially related to learning English. Community service entitled